RANCANG BANGUN SISTEM INFORMASI PRESENSI SISWA PADA SMP MUHAMMADIYAH 1 PASURUAN DENGAN MENGGUNAKAN BARCODE - Syaifulloh, Ali; Wahyuningsih, Dian (DINAMIKA DOTCOM, 2013)
This research aims to design and build student attendance system in SMP Muhammadiyah 1 Pasuruan using barcodes that can facilitate in making the required attendance reports every month and incidental by education authorities .The method used in this study consists of two methods , the method of data collection and system development methods . In the method of data collection was observation , interviews, and literature . While the method of system development activities include design , data analysis , system design , system evaluation , application development , system testing , documentation and report preparation .From the research that has been done can be obtained in the form of creation results Presence student information system combined with barcode and the establishment of a database system which is applied to the system as an alternative student attendance to present the report student attendance SMP Muhammadiyah 1 Pasuruan requested by the education department .Â keywords:Informatian System, Presence, Barcode